Learning Natural Science Through Interactive Resources - Becerra García, Eulalia; Yánez Rueda, Hugo; Mora Rosales, José (My University, 2025)
Learning Natural Sciences through interactive resources enhances the understanding of complex concepts by offering visual and hands-on experiences. These tools allow students to explore natural phenomena, perform simulated experiments and visualize processes invisible in real life. Objective: Examine how interactive tools influence the retention of complex natural science concepts. Methodology: It follows a positivist paradigm, with a quantitative approach, a field study and a sample of 60 elementary school students to whom a questionnaire was applied to measure knowledge before and after applying the interactive resources. Results: A course was created within the Moodle virtual learning environment focused on improving the learning of Natural Sciences with interactive resources elaborated in the technological tools: powtoon, Phet Interactive Simulations and H5p Interactive with selected topics of natural sciences based on their pedagogical relevance and the capacity of concepts to be exploited with interactive simulators. Conclusions: Interactive resources were developed to improve natural science learning, with technological tools that made the contents more interactive, visual and accessible.
Keywords: Learning; meaningful; natural; projects; sciences